Extending our hands to Jahai people / Puteri Rohani Megat Abdul Rahim - Megat Abdul Rahim, Puteri Rohani (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2022)
On the 3rd of September, 2020, a group of researchers from UiTM Perak Branch consisting of three teams of 11 lecturers conducted a com-munity service (CSR) for Jahai people at Kg. Sg Tiang in Royal Belum, Perak. The aim of the CSR was to establish contact with the Jahai community and school children as well as to understand the lives of the community in Kg. Sg Tiang. They reached the site after a one-and-a -half-hour drive on a speedboat and was pleasantly greeted by Mr Mohd Sarapi bin Shamsun, the headmaster of SK Sg. Tiang. Shortly after that, they conducted data collection on the students there and had the opportunity to observe Jahai adults during their English learning lesson.